2019
DOI: 10.3899/jrheum.190019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Treatment on Damage and Hospitalization in Elderly Patients with Microscopic Polyangiitis and Granulomatosis with Polyangiitis

Abstract: Objective.Age is a risk factor for organ damage, adverse events, and mortality in microscopic polyangiitis (MPA) and granulomatosis with polyangiitis (GPA). However, the relationship between treatment and damage, hospitalizations, and causes of death in elderly patients is largely unknown.Methods.Consecutive patients from Sweden, the United Kingdom, and the Czech Republic diagnosed between 1997 and 2013 were included. Inclusion criteria were a diagnosis of MPA or GPA and age 75 years or more at diagnosis. Trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…IV MP was associated with a nearly 3-fold higher risk of serious infection at 3 months, and a 6-fold higher risk of new-onset diabetes mellitus (8). Other studies also found IV MP to be independently associated with severe infections (10,11), and treatment-related damage (12).…”
Section: Methodsmentioning
confidence: 93%
“…IV MP was associated with a nearly 3-fold higher risk of serious infection at 3 months, and a 6-fold higher risk of new-onset diabetes mellitus (8). Other studies also found IV MP to be independently associated with severe infections (10,11), and treatment-related damage (12).…”
Section: Methodsmentioning
confidence: 93%
“…As disease severity at presentation is known risk factor for permanent organ damage (29), this finding likely reflects the benefit of attenuated disease activity achieved with therapy. There was no increased rate of hospitalisation or length of stay within 12 months of treatment (30).…”
Section: Discussionmentioning
confidence: 81%
“…Amongst other factors, advancing age has previously been associated with a higher degree of long term damage and this patient group are potentially more frail with increased susceptibility to any potential treatment related morbidity (29). In a follow-up study of their previously reported cohort, Weiner et al set out to address this by evaluating the potential association between end organ damage and hospitalisation rates with therapy at one and two years (30). In doing so, they identified that amongst patients >75 years the use of cyclophosphamide or rituximab was actually associated with a lower rate of damage (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to treatment regimens containing CYC, the use of RTX alone may reduce the risk of bone marrow suppression. Research by Weiner et al (2020) has demonstrated that both CYC and RTX therapies can reduce permanent organ damage in elderly patients with AAV. However, the use of higher doses of glucocorticoids within the first 3 months is associated with treatment-related injuries and fatal infections.…”
Section: Biologicsmentioning
confidence: 99%